Pengaruh Kualitas Produk dan Social Media Marketing Terhadap Repurchase Intention Melalui Keputusan Pembelian (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of product quality and social media marketing on purchase decisions and their impact on consumers' repurchase intention at Tomoro Coffee. A quantitative approach was used, with data collected through questionnaires distributed to respondents who are consumers of the studied product. The study involved 250 participants selected using accidental sampling. Data analysis was conducted using Partial Least Squares (PLS) with the SmartPLS software. The results indicate that both product quality and social media marketing have a positive and significant effect on purchase decisions. Furthermore, purchase decisions also have a positive and significant influence on repurchase intention. These findings highlight the importance of product quality and digital marketing strategies in fostering consumer loyalty through purchase decisions